Insurers risk-taking behaviour in an emerging economy: unpacking the linear and nonlinear effects of enterprise risk management and corporate governance - Sylvester Senyo Horvey (Cogent Business & Management)
This study explores both the linear and nonlinear effects of corporate governance (CG) and enterprise risk management (ERM) on insurers’ risk-taking preferences. This paper was analysed using the generalised method of moments and the dynamic panel threshold estimation techniques based on a sample of 33 insurance companies in Ghana between 2015 and 2021. The results from the linear regression show that ERM significantly and positively influences insurers’ risk-taking, indicating that insurance companies with effective ERM programs are more inclined to assume higher risks. Additionally, the empirical findings indicate that risk-taking is negatively associated with gender diversity but positively influenced by board independence and size. The study further reveals nonlinearities between ERM, CG and risk-taking. The empirical evidence indicates that a strong ERM system enhances the risk-taking behaviour of insurers when it exceeds the threshold level and vice versa, implying a U-shaped relationship. Thus, an effective ERM program promotes better insurance risk-taking decisions. Also, the study presents a U-shaped relationship between board independence and insurers’ risk-taking. Contrarily, board size, and gender diversity reveal a relationship with an inverted U-shape, implying that the board makes less risky decisions when they are large, gender diversified and there are more females on the board. Policy implications are provided.